Analisis Pendapatan Dan Keberlangsuhan Usaha Terhadap Kenaikan Tarif Pajak 12 % Pada Usaha Mikro, Kecil Menengah (UMKM) Di Kota Medan - Hasibuan, Rahmawaty; Eka Rizki Meiwinda; Sunanto; Siska Almaniar; Willy Wijayanti (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Tax is one of the income in Indonesia and is a mandatory deposit paid to the state without any direct benefits, which is used for state needs and public welfare. There are many types of taxes in Indonesia, one of which is Value Added Tax (VAT). VAT is closely related to Taxpayers who are Taxable Entrepreneurs, VAT is collected on purchase/sales transactions carried out by Taxpayers, both Individuals and Corporate Taxes. On January 1, 2025, the government increased the VAT rate from 11% to 12%. The increase in VAT aims to increase state revenues so that in the long term it can support development and encourage economic recovery. The study aims to determine the impact of the increase in VAT rates on income and business continuity of UMKM in Medan City. The data analysis method used in this study is the multiple linear regression analysis method. The results of the study based on the multiple linear regression analysis method show that the income and business continuity variables have a significant positive effect on the 12% tax rate variable on UMKM in Medan City. Data was taken from 36 UMKM in Medan City. The results of the study stated that the increase in VAT to 12% has a positive impact, namely that it will increase state revenue to be redistributed to the community. Meanwhile, the negative impacts that will arise include increasing prices of goods and services, increasing inflation, and decreasing people's purchasing power.